Survey Of Services Jend. Sudirman-Jalan A.P. Pettarani, At Maros City, South Sulawesi Province: Survei Pelayanan Persimpangan Jalan Jend. Sudirman-Jalan A.P. Pettarani Di Kota Maros Provinsi Sulawesi Selatan - Azis, Abdul (Procedia of Social Sciences and Humanities, 2022)
This study aims to determine the level of service at the intersection of Jl. Jend. Sudirman-Jl. A.P. Pettarani Maros City often experiences a slowdown in the morning, afternoon, and evening. The research uses survey methods and the data processing method uses quantitative methods based on statistical data. The data required for data collection and collection includes the following data: the vehicle population is taken for 6 (six) working days. The location of this research will be carried out on the Jl. Jend.. Sudirman-Jl. A.P. Pettarani Maros City. Data analysis includes vehicle characteristics. Based on observations at the intersection of Jl. Gen. Sudirman-Jl. A.P. Pettarani Maros City often experiences a slowdown in the morning, afternoon, and evening. The volume of the vehicle is quite large. In addition, it causes traffic slowdown at intersections. In addition to the distance from other alternative roads that can be crossed, the level of deceleration on Jl. Jend.. Sudirman-Jl. A.P. Pettarani Maros City used to be often jammed so that there was a slowdown when approaching the Horse Statue Monument. Traffic regulation at this intersection is assisted by traffic lights, but there are still long queues, especially during peak hours. Meanwhile, the development of road facilities is not matched by the growth of traffic volume, so that the intersection does not serve the traffic volume.